Tata Kelola dalam Penyediaan Air Bersih sebagai Layanan Publik (Studi Kasus Peran Pemerintah Kota Bekasi dan Perumda Tirta Patriot) - Abdi Dzul Fahmi; Dadang Suwanda; Andi Azikin (Ekonomis: Journal of Economics and Business, 2026)
This study examines governance trap in clean water provision as a public service in Bekasi City — a metropolitan city of 2.89 million inhabitants achieving only 64.5% piped water coverage in 2024, far below the national Minimum Service Standard (SPM) of 90%. Using a qualitative case study approach with 12 key informants (928 minutes of interviews), field observations, and document analysis during March–May 2025, this study integrates four theoretical frameworks: New Public Service, Good Governance, Institutional Coordination, and Principal-Agent Theory. Key findings reveal: (1) service failure is multidimensional with governance deficits across all four dimensions simultaneously; (2) cumulative investment gap of IDR 878 billion over five years (88.4% of actual needs); (3) the Coordination Team mandated by West Java Governor Regulation No. 38/2020 remains unformed, creating a coordination vacuum; (4) tariff IDR 4,850/m³ below production cost IDR 5,920/m³ generating IDR 48.3 billion cumulative deficit. This research contributes three conceptual innovations: the governance trap concept as a novel diagnostic framework, a proposition on principal-agent relationship quality as the critical determinant of local government enterprise performance, and a proposition on BUMD as a bridge organization in collaborative governance. A four-pillar optimization strategy targeting 90% SPM by 2034 is proposed.